The role of allied healthcare professionals in head and neck cancer surveillance: A systematic review. (22nd November 2019) - Rocke, John; Mclaren, Oliver; Hardman, John; Garas, George; Smith, Matthew E; Ishii, Hiro; Constable, James; Tikka, Theofano; Wie Liu, Zi; Williams, Richard; ,
Abstract: Objectives: The roles of Allied Health Care Professionals (AHPs) in Head and Neck Cancer (HNC) are wide ranging but not clearly defined. Inter‐regional variability in practice results from a lack of standardisation in approaches to the Multidisciplinary Team (MDT) make‐up and structure. Traditionally, the follow‐up of HNC patients is clinician led with multiple scheduled follow‐up appointments. The increasing population of HNC patients provides logistical, monetary and efficiency challenges. This systematic review presents the roles of the multiple AHP sub‐groups in HNC with the aim of presenting how their differing skill sets can be integrated to modernise our approach in follow‐up. Design: We searched MEDLINE, Embase, the Cochrane Library, NIHR Dissemination Centre, The Kings Fund Library, Clinical Evidence, National Health Service Evidence and the National Institute of Clinical Excellence to identify multiple subgroups of AHPs (Dentists, Speech and Language Therapists, Dieticians, Physiotherapists, Psychologists, Clinical Nurse Specialists) and evidence of their role in HNC follow‐up. Evidence not directly relating to HNC follow‐up was excluded. Setting and Participants: This Systematic Review was undertaken online by the Integrate (UK ENT Trainee National Collaborative) Head and Neck Subcommittee. Main Outcome Measures: Most evidence was of low‐quality, and the broad nature of the protocol provided a wide variety of study models. Two authors screened the articles for relevance to the topic before final analysis. Results: The main role identified was improvement in Quality of Life and symptom control rather than detecting recurrence. We also demonstrate that it is possible to stratify HNC follow‐up patients using their received treatment modality and Distress Thermometers to identify groups who will require more intensive AHP input. Conclusions: HNC follow‐up covers a broad group of patients with differing needs. As such, a blanket approach to this phase of treatment is likely to be less effective than a patient‐led model where the group of AHPs are employed on a needs basis rather than at set time points. This will likely lead to greater patient satisfaction, earlier detection of recurrence and efficiency savings.